"Innovate or Perish?": Companies under crisis - Elena Shakina; Angel Barajas (European Research on Management and Business Economics (ERMBE), 2020)
This paper tests the behavioral firm theory by examining exogenous economic shocks to explore whether switching to an innovative strategy is always reasonable. A quasi-experimental design - difference-in-difference - has been run on 1000 companies for 11 years to explore the consequences of strategic shifts towards innovations. It is found that companies that introduced innovations do not have any substantial differences from those that kept the "status quo". However, those few companies that decided to follow a proactive strategy during crisis by introducing new R&D projects outperform their rivals in the medium-term. A nonlinear relation between the decision to switch to an innovative strategy and related performance suggests that returns to scale exist. Only those cases of innovative shifts that enable the growth of more than 50% in intangible assets on average and more than 30% in a recession appear to be successful and lead to higher performance for companies.
Keywords: 650; Crisis; Difference-In-Difference; Innovative strategy; Investment in innovation; Performance; Threshold of innovation